2018
DOI: 10.21608/jacb.2018.35195
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis for Yield and its Components in Bread Wheat

Abstract: Eight bread wheat cultivars were used to study some earliness and yield and its component traits. The parental cultivars were employed to produce 28 F 1 hybrids following 8 x 8 half Diallel crossing without reciprocals. The seeds of 28 F 1 hybrids and their parents were planted to estimate mean squares due to parents and their crosses which were significant for all studied traits. The parental variety P 3 was the best parent for earliness. However, P 8 was the best for remained traits. The crosses (P 1 x P 4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
0
0
Order By: Relevance
“…The analysis of variance table (1) shows that the parental genotypes differed significantly at the level of probability (1%) for all studied traits except for the number active tillers plant -1 , which differed significantly from the level of probability (5%), while the first-generation crosses (Table 2) differed significant in all the studied traits at the level of probability (1%) except for the characteristic of the number of spikelet's, spike -1 , which differed significantly at the level of probability (5%). This result agreed with [12], [13].…”
Section: Resultssupporting
confidence: 88%
“…The analysis of variance table (1) shows that the parental genotypes differed significantly at the level of probability (1%) for all studied traits except for the number active tillers plant -1 , which differed significantly from the level of probability (5%), while the first-generation crosses (Table 2) differed significant in all the studied traits at the level of probability (1%) except for the characteristic of the number of spikelet's, spike -1 , which differed significantly at the level of probability (5%). This result agreed with [12], [13].…”
Section: Resultssupporting
confidence: 88%
“…It is noted from the tables of the analysis of variance (1) that the parental genotypes differed significantly at the level of probability (1%) in all the studied traits except for the number of active tillers plant -1 differed significantly from the level of probability (5%), and from the table of the analysis of variance (2) It was found that the first-generation hybrids were significant in all the studied traits at the level of probability (1%) except for the number of spikelet's spike -1 differed significantly from the level of probability (5%), This is evidence of the genetically different parental genotypes, as well as the difference in crosses resulting from half-diallel crosses. This result agreed with [12,13].…”
Section: Resultssupporting
confidence: 86%